Cosmogenic (3)He in terrestrial rocks: The summit lavas of Maui - Craig, H. (1986)
We have identified terrestrial cosmic rayproduced (3)He in three lava flows on the crest of Haleakala Volcano on Maui, 3 km above sea level, and ≈0.5 million years old. Although these lavas, like all oceanic basalts, contain primordial (3)He from the mantle, the “cosmogenic” component ((3)He(C)) can be identified unambiguously because it is extractable only by high-temperature vacuum fusion. In contrast, a large fraction of the mantle helium resides in fluid inclusions and can be extracted by vacuum crushing, leaving a residual component with (3)He/(4)He ratios as high as 75× those in the atmosphere, which can be liberated by melting the crushed grains. Cosmogenic (3)He is present in both olivines and clinopyroxenes at 0.8-1.2 × 10(-12) ml(STP)/g and constitutes 75% ± 5% of the total (3)He present. The observed (3)He(C) levels require a cosmic ray exposure age of only some 64,000 years, much less than the actual age of the lavas, if there is no erosion. Using a model that includes effects of uplift or submergence as well as erosion, we calculate an apparent “erosion rate” of the order of 8.5 m/10(6) years for the western rim of the summit crater, as an example of the application of measurements of cosmogenic rare gases to terrestrial geological problems.